The Relationship Between Ego Strength, Emotional Intelligence, and Clinical Skills Performance in Preclinical Medical Students - Jerlia Wardayani; Sukadiono Sukadiono; Roni Subagyo; Muhamad Reza Utama (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Academic stress is associated with mental disorders such as depression, anxiety, physical,and academic challenges. Medical students are particularly susceptible to high levels ofstress due to demanding academic workloads, intense competition, and prolonged studyperiods. Assessments like Objective Structured Clinical Examination (OSCE), whichevaluate students' clinical skills, also contribute to stress. One of the key factors insuccessfully facing this test is ego strength and emotional intelligence. This study aims toinvestigate the relationship between ego strength, emotional intelligence, and clinicalskills performance. A quantitative research design employing an analytical observationalapproach and a cross-sectional methodology was utilized. The instrument used tomeasure academic stress is the MMPI-1, while emotional intelligence is the TEIQue-SF.A total sampling method was employed for participant selection. The research findingsshow that the majority of respondents have low levels of ego strength (60%), a mediumlevel of emotional intelligence (77%), and OSCE scores was predominantly A grades.There was a weak association between emotional intelligence and OSCE performance (p= 0.784). Similarly, relationship between ego strength and OSCE performance (p =0.314). It is important that the identified relationships are correlative rather than causaland their impact is not statistically significant.